Sandra McGee Deutsch, Las Derechas. The extreme Rigth in Argentina, Brazil, and Chile, 1890-1939, Stanford, Stanford University Press, 1999 - Lvovich, Daniel (2001)
Fil: Lvovich, Daniel. Universidad Nacional de Gral. Sarmiento.